Device for Simulating Fluid Microgravity Environment Based on Magnetic Compensation Method and Research on Magnetic Fluid Lubrication Performance of Oil Film Bearing - Han Peng; Linjian Shangguan; Hai Zhang (Advances in Materials Science and Engineering)
At present, with the rapid development of the material market, the requirements of high performance and high precision of materials are increasingly exposed. Nanomagnetic fluid materials are more and more widely used in oil film bearings, but their compressive strength and performance are insufficient, which is difficult to meet the current requirements of material chemical properties. First of all, a device for simulating a microgravity environment with magnetic compensation is fabricated. Then, in the microgravity environment, according to the different proportions of magnetic solid particles, the base carrier liquid and the surfactant are mixed to produce nanomagnetic fluid and the nanomagnetic fluid with different composition proportions is prepared by adjusting the proportion of ferrous and ferric ions. Finally, the lubrication performance of oil film-bearing magnetic fluid with different composition ratios was tested. The results show that when the ratio of Fe2+ to Fe3+ is between 11 : 20 and 13 : 20, the MHD (magnetohydrodynamics) lubrication performance of oil film bearing is in the peak region. When the ratio is 3 : 5, the best lubrication performance can be achieved. When it is slightly higher than this ratio, the oxidation rate is accelerated due to more ferrous ions. Although it can have a good lubrication effect, it is easy to cause the overall fluidity of oil film-bearing magnetic fluid to deteriorate. Therefore, the oil film bearing nano-MHD with the ratio of 3 : 5 ferrous to ferric has the best lubrication performance in the microgravity environment simulated by magnetic compensation. Experiments have shown that when the magnetic fluid is heated in a magnetic field, the temperature gradient will cause the magnetization to change, which makes the magnetic force experienced by the liquid in each part different, causing convection. Therefore, by selecting the direction of the magnetic field and the heating surface, by applying an external magnetic field or promoting convection, or suppressing convection, convection in the opposite direction to the natural convection of gravity can also be realized. Moreover, magnetism can immediately promote high-temperature boiling, generate bubbles, and eliminate the generation of bubbles to promote heat transfer. With the above effects, the heat conduction between the heating wall and the liquid can be controlled, and its practical and potential application fields are very wide.